The Influence of Corporate Lobbying on Federal Contracting. (16th May 2019) - Dusso, Aaron; Holyoke, Thomas T.; Schatzinger, Henrik
Abstract : Objective: Corporations spend significant resources lobbying for billions of dollars in federal procurement contracts, yet this important opportunity to assess the political influence of business has gone unstudied by scholars of business politics. We study it here. Methods: We approach it by analyzing the influence of direct lobbying of five federal departments, along with data on the lobbying of, and campaign contributions to, members of Congress on patterns of contract awards broken out by congressional districts. Results: Our analysis reveals that while there are many reasons to expect lobbying Congress to produce valuable contracts, we instead find that it is the direct lobbying of executive branch agencies that is most likely to bring big rewards. Conclusion: These results highlight the importance of studying corporate political power outside of the legislative branch, suggesting that it is the long‐term relationships that lobbyists build with bureaucrats that yield the most lucrative contracts.